Книговидання на Волині у ХХ столітті (до проголошення незалежності України) - Мациборська, Олена М.; Matsyborska, О.М. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті проаналізовано розвиток книговидання на Волині протягом ХХ століття. Відображено історичні та суспільно-політичні умови, в яких працювали волинські видавці, та вплив цих умов на особливості волинського книговидання. Зазначено, що характерними рисами видавничої справи на Волині у ХХ ст. є історично зумовлена тривала криза та українсько-польська «двокультурність». Запропоновано періодизацію книговидавничої справи краю, причому наголошено, що розвиток волинського книговидання дещо відрізняється від загальноукраїнського; охарактеризовано книговидання кожного періоду. The article analyzes the development of book publishing in the Volyn region in the twentieth century. It is noted that its features are historically and politically due to prolonged crisis, as well as Ukrainian-Polish «bicultural» publishing traditions. Disclosed historical and socio-political context in which the publishers worked Volyn, as well as the impact of these conditions on the characteristics of Volyn publishing. The development of industry in the region significantly influenced anti-Ukrainian policy of Russia and Poland, War, totalitarian policy of the USSR. The rich tradition of publishing Volyn were virtually wiped out: closed all official publisher, liquidated «samizdat», from 1966 to 1990 in the area was not published any books. The revival of the publishing industry has been made possible only because of political reform in the Soviet Union and Ukraine's independence. The paper proposes a periodization Volyn publishing of the last century, which is compared with the general periodization of Ukrainian book publishing at the time.
Publishing in Volyn in the Twentieth Century (before the Proclamation of Independence of Ukraine)
Keywords: книговидання; publishing; Волинь; Volyn; «двокультурність»; «bicultural»; криза; crisis; "самвидав"; «samizdat»; цензура; censorship; періодизація; periodization